Job-Task Analysis of Vision Rehabilitation Therapists. (March 2020) - Connors, Elyse M.; McMahon, John M.; Lee, Helen
Introduction: One way to understand a profession is to examine the job tasks undertaken by professionals within the field. The profession of vision rehabilitation therapy is examined by finding the frequency at which 100 specific job tasks are performed on average by current vision rehabilitation therapists (VRTs). Fifty-one of the job task frequencies are compared to 1989 frequencies for changes across the last 28 years. Methods: An anonymous online survey was carried out with current and recently retired VRTs. Participants were asked to rate the frequency at which they perform 100 specific job tasks and 13 demographic questions. Results: One hundred eighty-nine practitioners completed the survey. Mean frequencies for the 100 job tasks fell between a low of 1.08 (slightly above "do not perform the task") for "writes grants for funding of agency services" and a high of 5.51 (above "perform 4 or 5 times a week") for "writes case notes and reports for documentation." Half of the 51 comparable job tasks indicated statistically significant changes in frequency across the 28-year period. Discussion: Statistically significant changes in job task frequencies occurred across job roles of teaching, case management, and professional or administrative activities, indicating that many aspects of the therapist's job have changed. Individualized teaching remains a common aspect of the job, personalizing the skills taught and the teaching methods, for the individual client. VRTs are less frequently providing consultation to medical and community organizations. Implications for practitioners: The results presented provide an understanding of current job tasks of a practicing VRT. Understanding the changing trends of job tasks may inform university personnel preparation programs to better prepare students for employment demands. Decreasing community outreach may negatively affect the visibility of blind rehabilitation services and inadvertently affect referrals for vision rehabilitation therapy services.